Destruction of the abdominal wall and its sequelae in sepsis of digestive origin - Martínez, Luis (Cirugía del Uruguay, 2002)
There are multiple aspects, which affect treatment of patients that carry a digestive origin sepsis and most involve, one way or another, abdominal wall integrity. Currently, the greater pressure for.solutions involving integral anatomo functional restitution, constitutes a logic and growing demand which necessarily leads to the critica! analysis of therapy options cmTently applied in parietal management and closure